Clear cell sarcoma: state-of-the art and perspectives. Issue 3 (4th March 2023) - Wetterwald, Laureline; Riggi, Nicolò; Kyriazoglou, Anastasios; Dei Tos, Giovanni; Dei Tos, Angelo; Digklia, Antonia
ABSTRACT: Introduction: Clear cell sarcoma (CCS) is an ultrarare soft tissue sarcoma (STS) with a poor prognosis due to its propensity to metastasize and its low chemosensitivity. The standard treatment of localized CCS consists of wide surgical excision with or without additive radiotherapy. However, unresectable CCS is generally treated with conventional systemic therapies available for treatment of STS despite the weak scientific evidence to support its use. Areas covered: In this review, we discuss the clinicopathologic characteristics of CSS, as well as the current treatment landscape and future therapeutic approaches. Expert opinion: The current treatment strategy of advanced CCSs, based on STSs regimens, shows a lack of effective options. Combination therapiesin particular, the association of immunotherapy and TKIs, represent a promising approach. Translational studies are needed in order to decipher the regulatory mechanisms involved in the oncogenesis of this ultrarare sarcoma and identify potential molecular targets.